Fast Assessment of Rotor Barrier Dimensional Allowances in Synchronous Reluctance Machines - Carlos Madariaga; Cesar Gallardo; Juan A. Tapia; Werner Jara; Andres Escobar; Michele Degano (IEEE Access)
Tolerance analysis on synchronous reluctance machines (SynRM) is mandatory if accurate refinements of the rotor structure are adopted, a must for low-ripple applications However, the impact of manufacturing/dimensional tolerances or material degradation has been scarcely included in the design steps for SynRMs obeying complexity and time-requirement reasons. The paper provides an analysis of rotor barrier dimensional allowances in synchronous reluctance machines by utilizing a semi-analytical approach. This method is not only fast yet it also generates a substantial number of results that allows to evaluate the influence of dimensional deviations on the machine’s performance. The proposed performance evaluation method is validated in four machines by direct finite element (FE) simulations, showing good agreement and low computational burden. Once validated, the method is applied to perform a brute-force search in a single-barrier 4-pole machine with different combinations of dimensional allowances, obtaining a significant reduction in computational time compared to traditional direct FE evaluation. The paper concludes with a description of the proposed methodology and its applicability to other SynRM designs. This opens the possibility of quickly analyzing tolerances in SynRMs and improving their performance by evaluating different dimensions and position of flux barriers.